Meningkatkan Motivasi Belajar Al-Qur’an Bagi Anak-Anak Dalam Program Maghrib Mengaji Di Desa Mekar Sawit Kabupaten Langkat - Hasanuddin, Hasanuddin; Ujung, Amiruddin; Hidayat, Muhammad (Journal of Community Sustainability, 2025)
The Maghrib Mengaji program aims to foster children's love of the Quran and increase their motivation to learn and practice its contents. This research and activity was motivated by the low interest of some children in learning the Quran due to the influence of technology and a lack of spiritual guidance in their communities. The method used in this program is a participatory approach involving Quran teachers, parents, and community leaders. Activities include habituating Quran reading after the Maghrib prayer, providing rewards, using engaging learning methods, and instilling religious values ​​through stories and role models. The implementation results indicate an increase in children's enthusiasm and discipline in participating in Quran recitation activities, as well as a growing sense of responsibility and habit of worship. Thus, the Maghrib Mengaji program has proven effective in increasing children's motivation to learn the Quran, while simultaneously strengthening religious values ​​within the community.